Rumen fermentation profile and methane mitigation potential of mango and avocado byproducts as feed ingredients and supplements - Hassan Jalal; Ekin Sucu; Damiano Cavallini; Melania Giammarco; Muhammad Zeeshan Akram; Büşra Karkar; Min Gao; Luigi Pompei; Jorge Eduardo; Paraskevi Prasinou; Isa Fusaro (Scientific Reports)
Abstract Fruit byproducts represent a sustainable alternative to conventional feed for ruminants, addressing food-feed competition and environmental concerns, particularly through their potential to reduce enteric methane emissions via bioactive compounds. This study explored the use of mango and avocado byproducts as feed ingredients and supplements. In experiment 1, mango peel (MP), mango seed kernel (MSK), mango seed coat (MSC), avocado peel (AP), and avocado seed (AS) were independently tested to determine their chemical composition, in vitro digestibility, and rumen fermentation parameters, including gas production and methane emissions. In experiment 2, rumen fermentation parameters were evaluated across five treatment groups: The control group received 200 mg of alfalfa hay alone, without any supplementation. The remaining four groups each received 200 mg of alfalfa hay as the basal diet, supplemented with 15 mg of one of the following microencapsulated extracts: mango peel extract (MPE), avocado peel extract (APE), mango seed kernel extract (MSKE), or avocado seed extract (ASE). Both experiments were conducted over three runs, with each run including three replicates per treatment group, resulting in a total of nine replicates per group. Data were analyzed using linear mixed models with Bonferroni-adjusted pairwise comparisons (p < 0.05). MSK had the highest crude protein content, whereas AP had the highest ether content. MSC and AP presented the highest fiber fractions. AP and MP showed higher total phenolic content and antioxidant capacity. In experiment 1, AS, MP and MSK resulted in greater in vitro dry matter digestibility, and cumulative gas production compared to MSC and AP. Acetate to propionate ratios were higher in AS, MSC, and MSK. Methane production (ml/g dry matter incubated) was highest in MSK (43.7), while AP (19.8) and MSC (18.7) produced the lowest, representing almost 55% reduction compared to MSK (P < 0.001). MP (40.9) and AS (42.2) had intermediate methane values. Ammonia nitrogen was highest in AP and lowest in MSC. In experiment 2, MSKE, ASE and the control had the highest cumulative gas production, whereas APE reduced methane production by 16% compared to the control and lowered the acetate-to-propionate ratio. Compared with the control, all the encapsulated extracts lowered the ammonia nitrogen concentration. Overall, MP, MSK, and AS have emerged as the most promising ingredients because of their relatively high digestibility, and fermentation efficiency, whereas APE and MPE have potential as feed supplements for reducing in vitro methane production.